Assessment of aluminum induced genotoxicity with comet assay in wheat, rye and triticale roots - (:unkn) unknown (Parlar Scientific Publications, 2015)
Aluminum (Al) toxicity is one of the major constraints that limits plant growth and development in acidic soils (pH<5). The present study describes the assessment and comparison of time-dependent nuclear damage under Al toxicity in three close related agronomic plant roots (Triticum aestivum (wheat), Seeale cereale (rye) and their hybrid Triticosecale wittmack (triticale)) performed by single cell electrophoresis (comet assay). The wheat, rye and triticale roots (∼1 cm) were exposed to 100 νM AlCl3 at 15, 30, 60 and 120 min. In Al-treated cells, the most informative measure of DNA damage induced by Al was the DNA tail, olive tail moment and tail intensity. All of the measurement values showed that the first sign of the genotoxic effect was visible at the 15th min in wheat, rye and triticale. The increase in DNA tail was most distinctive in wheat at 15 min. The DNA tail rates became similar after 30 min, and were steady up to 120 min comprising 9.1% in wheat, 9.2% in rye and 9.5% in triticale. Al toxicity decreased the olive tail moment after 120 min, and it was most significant in wheat. Comet assay revealed that the tail intensity represented 8.9, 10.9 and 7.3-fold increases in wheat, rye and triticale, respectively. In conclusion, Al-induced increase in migrated DNA, revealed by comet assay, may be considered as an indicator of acute DNA damage in the root tips of wheat, rye and triticale within a time range from 15 to 120 min.
Keywords: Al toxicity; Comet assay; Root; Rye; Triticale; Wheat